typo/graphic days 6 - Panayides, Angelos (My University, 2021)
typo/graphic days is an annual event of lectures and workshops on typography and graphic design organized by the The Semiotics and Visual Communication Lab (SVC Lab) of the Department of Multimedia Lab, the Language and Graphic Communication Research Lab, at the Cyprus University of Technology, supported by the Cyprus Association of Graphic Designers and Illustrators.
Keywords: Poster Design; Biennale; Exhibition